Engineering Design, Implementation, and Sensing Mechanisms of Wearable Bioelectronic Sensors in Clinical Settings - Dkhar D.S.; Kumari R.; Mahapatra S.; Divya; Chandra P. (My University, 2025)
Wearable sensing devices have transformed the hourly analysis of events such as body signals and environmental risks into real-time monitoring in minutes or seconds. Wearable sensors have facilitated the ability to obtain useful data by monitoring the physiological parameters and activities of an aided and a healthy individual. Wearable devices employ detectable biomarkers in the human body, such as in tears, saliva, interstitial fluid, sweat, and so on. These can deliver relevant information on human health, online activity monitoring, and therapeutic treatments. This section outlines the significance of sample types and associated biomarkers as indicators in the development and manufacturing of wearable biosensors. We have emphasized the most recent advances of wearables based on skin-like and textile, giving attention to personalized health monitoring to record signals of motion and physiological and body fluid investigation. Furthermore, this review categorizes wearable biosensors based on the sensing mechanism, electrochemical, optical, and mechanical. Additionally, the recent wearables related to the detection of the newly havoc-causing pandemic, COVID-19, and the future perspective for the development of much more advanced and potent wearable biosensors have been highlighted. The final section highlights unmet difficulties and gaps in wearable sensors in personalized therapy. © 2022 Wiley-VCH GmbH.